The factors influencing selection of Islamic credit card among muslim: case study in Oasis Ara Damansara / Nur Zahidah Zulkifli - Zulkifli, Nur Zahidah (Faculty of Business and Management, 2018)
The public acceptance of Islamic credit card in Malaysia's banking industry can be seen in favourable side. Credit card is one of the many facilities available for consumer to make financial transaction without carrying cash. Unlike conventional credit card, Islamic credit card give Muslim consumer an alternative to use the credit card facilities without have to worry about themselves being involve with activities prohibited in Sharia' such riba (interest) and gharar (uncertainty). The main purpose of this paper is to identify the factors that influence Muslim to select Islamic credit card. This study is based on a questionnaire survey conducted in Oasis Square Ara Damansara, Selangor. 183 questionnaires were collected from the respondents by using sfratified sampling technique. Based on an extensive review of literature, this paper is to identify the relationship between religious beliefs, convenience, social influences, attitude toward debt, and the Muslim selection towards Islamic credit card. This research used several data analysis method to generate the results included the frequency analysis, descriptive analysis, regression analysis, correlation analysis, and reliability analysis. Findings of this research shows that religious belief and social influence are the factors to Muslim's selection of Islamic credit card. Both factors are believed to have influenced the preference of Muslim to choose Islamic credit card. The result is expected to be used as a guidance for Islamic bankers in promoting Islamic credit card.